2009
DOI: 10.1007/s00467-009-1152-7
|View full text |Cite
|
Sign up to set email alerts
|

Fatal infection in children with lupus nephritis treated with intravenous cyclophosphamide

Abstract: A knowledge of the causes and risk factors of fatal infection in childhood lupus nephritis (LN) patients treated with intravenous cyclophosphamide (IVCY) is important to enable optimal treatment. During an 11-year period (1996-2007), severe infection cases occurred in 31/84 (36.9%) patients with 64 infection episodes in our central referral institution in southern Thailand. Fatal infections occurred in 13/31 (41.9%) patients, most (11/13, 84.6%) during the first infective episode. The major causative organisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
5
1
Order By: Relevance
“…In our study, more than one‐third of the children with serious infections had 3 or more such episodes, which is higher than what was reported in prior series . A study of children treated with cyclophosphamide for LN in Thailand reported that fatal infections occurred in 13 of 84 patients (15%) . The authors observed that previous treatment with pulse methylprednisolone, kidney disease, and fungal infection were associated with fatal infections in their population.…”
Section: Discussioncontrasting
confidence: 63%
“…In our study, more than one‐third of the children with serious infections had 3 or more such episodes, which is higher than what was reported in prior series . A study of children treated with cyclophosphamide for LN in Thailand reported that fatal infections occurred in 13 of 84 patients (15%) . The authors observed that previous treatment with pulse methylprednisolone, kidney disease, and fungal infection were associated with fatal infections in their population.…”
Section: Discussioncontrasting
confidence: 63%
“…We have previously reported finding 64 infection complications in 32 out of 84 SLE patients whose condition indicated treatment with intravenous cyclophosphamide (IVCY), a figure which is higher than in other studies 20 21…”
Section: Discussionmentioning
confidence: 76%
“…Infection is a common complication in SLE patients treated with IVCY therapy, as we previously reported, with opportunistic infections being the most common [ 21 ]. Severe infections were found in 36.9 % (31/84) of those cases, of whom 13 died (41.9 %).…”
Section: Discussionmentioning
confidence: 97%